Identifying the variables that favor the application of the course system instead of the annual system - Mahmood, Diaa Obaed; Alzawbaee, Obaid Mahmmood Mohsin (International Journal of Innovative Research and Scientific Studies, 2025)
Iraqi higher education institutions vary in the application of educational systems. Some of them adopt the annual system, others adopt the course system, and a few adopt the credit hour system. Technical education in Iraq has taken its share of applying the different educational systems, and recently it has relatively settled on applying the course system. A mathematical model was built to predict the likelihood of applying the course system instead of the annual system, using the logistic regression analysis technique, by identifying the independent variables with a significant impact from the total number of variables, which amounted to 13 variables. It was found that 7 variables were statistically significant, and they were arranged according to their importance. The tests proved the accuracy and strength of the model, as the percentage of correct classification reached 90.8%.